Postural factors contributing to reaching speed and accuracy. - Chimera, Nicole J.; Bohunicky, Sarah; Glazebrook, Cheryl; Scribbans, Trisha (International Journal of Occupational Safety & Ergonomics, 2025)
Objectives. Occupational reaching tasks performed with faulty postures may contribute to inefficient movement patterns that could lead to injury. Understanding relationships between posture and muscle activation during reaching tasks may elucidate movement patterns that increase occupational injury risk in workers. This study assessed whether postural factors and muscle activation predict forward reaching movement performance and accuracy. Methods. Predictor variables of forward shoulder posture (FSP), pectoral length, upper (UT), middle (MT) and lower trapezius (LT) and pectoralis major (PM) muscle activation, and UT:PM, MT:PM, and LT:PM co-activation during forward reaching were analysed for 56 individuals. Sequential linear regression equations assessed reaching variance. Results. For females, FSP, UT activation, and UT:PM co-activation explained 36% of reaction time (RT) variance, and MT:PM co-activation explained 14% of endpoint accuracy variance. For males, MT:PM co-activation explained 17% of movement time (MvT) variance, and FSP, MT:PM co-activation and MT explained 23% of accuracy variance. Conclusion. Increased co-activation was a predictor of movement performance; however, performance outcome variables differed between males (MvT) and females (RT). Muscle co-activation coupled with FSP and posterior shoulder muscle activation resulted in differences in predicting reaching performance variance. Practitioners might consider evaluating these muscle activation and postural factors in occupational reaching tasks. Trial registration: ClinicalTrials.gov identifier: NCT04944745.